Movement of boron from ulexite and colemanite minerals in sapwood and heartwood ofCryptomeria japonica - Kartal, Saip Nami; Terzi, Evren; Figen, Aysel Kanturk; Yoshimura, Tsuyoshi (NORTHEAST FORESTRY UNIV, 2020)
This study evaluated boron diffusion from raw boron minerals ulexite and colemanite with low water solubility in comparison to disodium octaborate tetrahydrate (DOT). Tests were conducted using sugi (Cryptomeria japonica(L.) f. D. Don) sapwood and heartwood blocks conditioned to 30, 60, and 90% target moisture content. The blocks were filled with the boron compounds through treatment holes and diffusion was observed at three assay zones across the blocks after 7, 30, 60 or 90-day incubation period at room temperatures. For comparison, ethylene glycol was also introduced into the holes to elevate boron diffusion. As expected, diffusion increased with increased moisture content and levels were higher at the 60% and 90% moisture levels compared to the 30% level. With some exceptions, boron levels did not follow consistent gradients with distance away from the treatment hole. Incorporation of ethylene glycol helped increase boron levels, even in heartwood blocks. Boron levels were higher from the ulexite source than from colemanite; however, DOT treatments resulted in the highest boron diffusion rates as a result of greater water solubility compared to both raw boron minerals. The results suggest that ulexite together with ethylene glycol may be useful in both sapwood and heartwood materials when kept at high moisture levels for extended periods.
Keywords: Boron; Remedial; Ulexite; Colemanite; DOT; Distribution; Sapwood; Heartwood; WOOD MOISTURE-CONTENT; DOUGLAS-FIR; DIFFUSION; BORATE; PERFORMANCE; FLUORIDE; Forestry